Analisis Kebutuhan dalam Pengembangan Modul Elektronik Berbasis STEM Materi Pelestarian Lingkungan - Wawan Darmawan (Jurnal Pendidikan Biologi Undiksha, 2024)
This research aims to conduct a needs analysis in developing STEM-based electronic modules with a focus on environmental conservation material. The research method used is descriptive qualitative research involving interviews, observation and questionnaires as data collection instruments. The research results show that there is an urgent need to update teaching materials, in line with the times and technological developments. The findings also indicate the need to develop teaching materials that are integrated with technology to facilitate students in understanding the concept of environmental conservation in a more interactive and applicable way. Apart from that, variations in learning approaches are crucial, because an approach is needed that is able to form critical thinking skills and improve students' skills in solving problems. It is hoped that the implications of this research can make a positive contribution to curriculum and learning development, so that students can be better prepared to face the demands of the ever-growing era.